مهام القناصل الأجانب في الجزائر خلال الحكم العثماني (1564م- 1830م) - حواسنية مروى (My University, 2025)
ABSTRACT : This thesis explores the roles of foreign consuls in Ottoman Algeria between 1564 and 1830, shedding light on the dual nature of their presence both as official diplomatic representatives and as actors engaged in covert activities shaped by the political and economic dynamics of the period. The study adopts a historical, analytical, and descriptive methodology to examine the various missions entrusted to consuls, their relationships with local Ottoman authorities, and their involvement in mediating conflicts, negotiating trade treaties, and overseeing the affairs of their nationals. In its applied dimension, the thesis presents case studies of selected French and American consuls, analyzing their writings and diplomatic reports to gain deeper insight into their functions and to highlight the contrast between their overt duties and covert roles in Ottoman Algeria. The findings reveal that consuls were not merely diplomatic intermediaries, but also played hidden roles that served the colonial and economic interests of their home countries including intelligence gathering, influencing political decisions, and, at times, fueling tensions between Algeria and European powers in preparation for future interventions. This study offers a valuable contribution to understanding the function of consulates in Ottoman Algeria, viewing them not only as channels of foreign representation, but also as tools of influence, surveillance, and strategic expansion. ---------------------------- الملخص: تتناول هذه المذكرة موضوع مهام القناصل الأجانب في الجزائر خلال الفترة العثمانية (1564-1830)، حيث تسلط الضوء على الدور المزدوج الذي اضطلع به القناصل ممثلو الدول الأوروبية، سواء من الناحية الرسمية الدبلوماسية أو من خلال نشاطات غير معلنة خضعت للسياق السياسي والاقتصادي لتلك الحقبة. اعتمدت الدراسة على المنهج التاريخي والتحليلي والوصفي لفهم طبيعة المهام التي كُلّف بها القناصل، وعلاقتهم بالسلطات العثمانية المحلية، وخاصة الدايات، إلى جانب دورهم في التوسط لحل النزاعات، وتنظيم المعاهدات التجارية، ومتابعة أوضاع رعايا دولهم. وفي الجانب التطبيقي، تطرقت المذكرة إلى دراسة حالات مختارة لبعض القناصل الفرنسيين والأمريكيين، من خلال تحليل كتاباتهم وتقاريرهم الدبلوماسية، بما يسمح بفهم أعمق لطبيعة مهامهم، وبيان الفروق بين الدور الظاهر والدور الخفي الذي لعبوه في الجزائر خلال العهد العثماني. وتُبرز النتائج أن القناصل لم يكونوا مجرد وسطاء دبلوماسيين، بل مارسوا أدوارًا خفية تخدم المصالح الاستعمارية والاقتصادية لدولهم، مثل جمع المعلومات، والتأثير في القرارات السياسية، بل وأحيانًا إثارة التوترات بين الجزائر والدول الأوروبية تمهيدًا لتدخلات لاحقة. تشكل هذه الدراسة مساهمة لفهم أعمق لدور القنصليات في الجزائر خلال العهد العثماني، ليس فقط كأجهزة تمثيل خارجي، بل كأدوات نفوذ ومراقبة واستعداد لمشاريع توسعية لاحقة.
Keywords: القناصل، الجزائر العثمانية، العلاقات الدبلوماسية، القناصل الفرنسيون، القناصل الأمريكيون، المهام الخفية، الامتيازات التجارية، القرصنة، معاهدات السلام